Active mud volcanoes on the continental slope of the Canadian Beaufort Sea. (24th September 2015) - Paull, C. K.; Dallimore, S. R.; Caress, D. W.; Gwiazda, R.; Melling, H.; Riedel, M.; Jin, Y. K.; Hong, J. K.; Kim, Y.‐G.; Graves, D.; Sherman, A.; Lundsten, E.; et al.
Abstract Morphologic features, 600–1100 m across and elevated up to 30 m above the surrounding seafloor, interpreted to be mud volcanoes were investigated on the continental slope in the Beaufort Sea in the Canadian Arctic. Sediment cores, detailed mapping with an autonomous underwater vehicle, and exploration with a remotely operated vehicle show that these are young and actively forming features experiencing ongoing eruptions. Biogenic methane and low‐chloride, sodium‐bicarbonate‐rich waters are extruded with warm sediment that accumulates to form cones and low‐relief circular plateaus. The chemical and isotopic compositions of the ascending water indicate that a mixture of meteoric water, seawater, and water from clay dehydration has played a significant role in the evolution of these fluids. The venting methane supports extensive siboglinid tubeworms communities and forms some gas hydrates within the near seafloor. We believe that these are the first documented living chemosynthetic biological communities in the continental slope of the western Arctic Ocean.